Efficacy and safety of plant-based therapy on recurrent aphthous stomatitis and oral mucositis in the past decade: a systematic review - Indah Suasani Wahyuni; Irna Sufiawati; Wipawee Nittayananta; Irma Melyani Puspitasari; Jutti Levita (Shahrekord University of Medical Sciences, 2021)
Oral mucosal inflammation is one of the oral diseases causing pain and reducing the quality of human life. The types of oral mucosal inflammation that commonly found were recurrent aphthous stomatitis (RAS) and oral mucositis (OM). Anti-inflammatory drugs, both synthetic and plant-based, have been used to treat RAS and OM. Plant-based drugs have been attracted the attention of some researchers to minimize the side effects of synthetic drugs. However, a comprehensive review addressing the use of plant-based drugs for RAS and OM therapy, including drug formulation and species of plant, has not yet been reported. Here, we reported the article review of 9 publications derived from the databases of PubMed, ScienceDirect, Cochrane Library, and other additional relevant works, in order to find the effectiveness and safety of plant-based drugs for RAS and OM therapy. This review was written by following the PRISMA guidelines, and the risk of bias of the articles was evaluated using the Oxford Quality Scoring System. It was found that the effective and safe drugs for RAS therapy contained acemannan from Aloe vera and curcumin from Curcuma longa, both in an oral gel formulation. For OM therapy, drugs contained curcumin from Curcuma longa; licorice from Glycyrrhiza glabra; Aloe vera and black mulberry from Morus nigra, in soft tablet, mouthwash solution or mucoadhesive film formulation. In conclusion, the most effective and safest plant-based therapy for RAS is Acemannan 0.5% in oral gel, whereas for OM is Licorice root extract 0.18 mg in mucoadhesive film.